Institutional duality and human resource management practice in foreign subsidiaries of multinationals - Stavrou, Eleni; Parry, Emma; Gooderham, Paul; Morley, Michael; Lazarova, Mila (Wiley, 2021)
We examine how institutional context affects the decisions that subsidiaries of multinational corporations (MNCs) make in pursuing particular human resource management (HRM) practices in response to institutional duality. Drawing on Varieties of Capitalism, along with the concept of intermediate conformity, we argue that the use of particular HRM practices by MNC subsidiaries will differ depending on both the combination of home and host institutional contexts, and on the nature of the particular practice under consideration. Using data from a survey of HRM practices in 1196 firms across 10 countries, we compare HRM practices in subsidiaries located and headquartered in different combinations of liberal and/or coordinated market economies. Our study suggests MNC subsidiaries conform only to the most persuasive norms, while exercising their agency to take advantage of the opportunities presented by institutional duality to adopt practices that distinguish them from indigenous competitors.
Keywords: HRM practices; MNCs; intermediate conformity; institutional duality; varieties of capitalism